Intrathoracic Sewing Needle: An Unusual Penetrating Injury in Two Children - Uguralp, Sema; Harma, Birsen; Karaman, Abdurrahman (Annals of Medical Research, 2021)
None
Keywords: Foreign Body, Sewing Needle, Thorax, Child